USAGE OF FINISHED DOSAGE FORMS IN THE MANUFACTURE OF EXTEMPORANEOUS POWDERS - A. V. Belyatskaya; I. I. Krasnyuk; I. I. (jr.) Krasnyuk; O. I. Stepanova; L. A. Korol; O. V. Rastopchina (Разработка и регистрация лекарственных средств)
The article highlights the importance of the pharmaceutical drugs manufacturing. There are analysis of prescriptions coming from pharmacies in Moscow. There are investigated the structure of extemporaneous drugs in accordance with the classification of the state of aggregation. The article revealed the use of ready-made drugs in extemporaneous technology of powder for children manufacturing. This circumstance is due to the lack of modern pharmaceutical substances in pharmacies. The article deals with the legal aspect of the problem.